Types of pediatric diabetes mellitus defined by anti‐islet autoimmunity and random C‐peptide at diagnosis. Issue 5 (5th March 2013) - Redondo, Maria J; Rodriguez, Luisa M; Escalante, Mirna; Smith, E O'Brian; Balasubramanyam, Ashok; Haymond, Morey W
<x xml:space="preserve">Abstract</x> Objective To test the hypothesis that anti‐islet autoantibody expression and random serum C‐peptide obtained at diagnosis define phenotypes of pediatric diabetes with distinct clinical features. Subjects We analyzed 607 children aged <19 yr consecutively diagnosed with diabetes after exclusion of 13% of cases with secondary diabetes (e.g., cystic fibrosis related, steroid induced) and 7.3% of cases lacking measurement of C‐peptide and/or autoantibodies. Methods Autoantibody positivity (A+) was defined as ≥1 positive out of GAD65, insulin, and ICA512 antibodies. Preserved beta‐cell function (β+) was defined as random serum C‐peptide at diagnosis ≥ 0.6 ng/mL. Body mass index (BMI) was measured at median 1.2 months after diagnosis. Characteristics at diagnosis and 2 yr (range 18–30 months) after diagnosis were compared among groups. Results Autoantibody expression and C‐peptide at diagnosis defined the following groups: A+β− (52.1% of the children), A+β+ (32.8%), A−β+ (12.5%), and A−β− (2.6%). These four groups differed in gender, race/ethnicity, and clinical characteristics at diagnosis [i.e., age, pubertal development, obesity/overweight, diabetic ketoacidosis, glycemia, and hemoglobin A1c (HbA1c)] and at 2 yr (i.e., clinical diagnosis, treatment, and HbA1c) (all p < 0.0001). Among all β+ children, C‐peptide >2 ng/mL was associated with lower HbA1c at onset (p = 0.0001) and, in the A+β+ subgroup, with higher frequency of achieving HbA1c < 7% at 2 yr (p = 0.03). All three patients (0.7% of total) with monogenic diabetes (maturity onset diabetes of the young, MODY) were A−β+ with C‐peptide between 0.6 and 2 ng/mL. Conclusions Anti‐islet autoantibodies status and serum random C‐peptide at diagnosis define four distinct phenotypes of pediatric diabetes with prognostic value.